Uji Aktivitas Antibakteri Virgin Coconut Oil (VCO) terhadap Pertumbuhan Bakteri Staphylococcus aureus - Niken Niken; Rahmi Novita Yusuf; Yanti Rahayu; Ibrahim Ibrahim (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Infectious disease is a disease that is generally caused by infection with pathogenic microorganisms. Staphylococcus aureus is a bacterium that causes the most common infectious disease. S. aureus infects tissues or organs and can cause disease which has characteristic signs of inflammation, necrosis, and abscess formation. Generally treat this Staphylococcus aureus bacterial infection by administering antibiotics. Long-term administration of antibiotics can cause negative effects on the body. One of the efforts to control S. aureus bacterial infection is by using herbal ingredients. VCO contains medium chain saturated fatty acids (Medium Chain Fatty Acid). Medium Chain Fatty Acid, namely lauric acid which can be broken down into monolaurin which has antibacterial properties. This study aims to determine whether VCO can inhibit the growth of S. aureus bacteria. This research is a laboratory experiment using the paper disc diffusion method (Kirby-Bauer). The sample used is Staphylococcus aureus bacteria. The concentrations used in this study were 20%, 40%, 60%, 80%, 100% and amoxicillin positive control and DMSO negative control. Data analysis was performed statistically with the One-Way Analysis of Variance (ANOVA) test. Data is normally distributed and homogeneous. The results showed that the antibacterial activity of VCO was shown to have inhibition against S. aureus bacteria with an average concentration of 20% with a diameter of 14.4 mm (strong), 40% diameter 14.5 mm (strong), 60% diameter 14.6 mm (strong), 80% diameter 14.6 mm (strong), 100% diameter 16.0 mm (strong), positive control amoxicillin 7.9 mm and negative control 0 mm. The results of the ANOVA test showed a value of p = 0.000 (sig. < 0.05) that there was a significant difference between all treatments with a positive control. It can be concluded that VCO was effective in inhibiting the growth of S. aureus bacteria, this was because the diameter of the VCO inhibition zone was larger than the positive control.